2014
DOI: 10.1016/j.exger.2014.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Losartan improves measures of activity, inflammation, and oxidative stress in older mice

Abstract: Sarcopenia is an age-related decline in skeletal muscle mass and function that is multifactorial in etiology. Age-related changes in the renin-angiotensin system (RAS), increased oxidative stress, and chronic inflammation likely all contribute to its development. Losartan, an angiotensin II type I receptor blocker (ARB) decreases RAS activity and likely influences oxidative stress and inflammation. Given this, we hypothesized that losartan would improve activity levels and parameters related to inflammation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 18 publications
2
40
0
Order By: Relevance
“…The biological basis of ARBs effect on chronic LGI involves the blockade of angiotensin II type 1 receptor leading to inhibition of NF-κB signaling (Kleiber et al, 2010). In animal experiments, sartans have been shown to reduce IL-6 levels (Lin et al, 2014), improve memory (Ongali et al, 2014) and motor performance (Villapol et al, 2012) and protect against muscle loss (Burks et al, 2011). Moreover, a recent meta-analysis of RCTs and observational studies reported that the use of ARBs can reduce incidence risks by 35% for cognitive impairment and by 20% for AD (Zhuang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The biological basis of ARBs effect on chronic LGI involves the blockade of angiotensin II type 1 receptor leading to inhibition of NF-κB signaling (Kleiber et al, 2010). In animal experiments, sartans have been shown to reduce IL-6 levels (Lin et al, 2014), improve memory (Ongali et al, 2014) and motor performance (Villapol et al, 2012) and protect against muscle loss (Burks et al, 2011). Moreover, a recent meta-analysis of RCTs and observational studies reported that the use of ARBs can reduce incidence risks by 35% for cognitive impairment and by 20% for AD (Zhuang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Along this line, losartan, an ang II type I receptor blocker, improved muscle activity and reduced inflammation in older mice [48].…”
Section: Cardiac Cachexiamentioning
confidence: 95%
“…Burks et al [20] indicate that the blockade of the AT1 receptor has beneficial effects on skeletal muscle remodeling in response to injury and conferring protection against disuse atrophy in sarcopenia by modulating the transforming growth factor-β (a known inhibitor of skeletal muscle regenerator) and Akt-mTOR pathways. In a study with older mice, it is suggested that treatment with losartan improves measures of physical function, decreases the inflammatory cytokine IL-6 and increases protective and antioxidant enzymes [21] . The Johns Hopkins University is conducting a clinical trial to see whether losartan can prevent the decrease in strength associated with aging, which will provide the evidence needed to clarify the association between sarcopenia and ARBs [22] .…”
Section: Angiotensin Receptors Blockersmentioning
confidence: 99%